Análise in sílico de proteínas relacionadas a sementes e identificação de microssatélites através da bioinformática - Meneghello, Geri Eduardo (2007)
The main reserve components in seeds are carbohydrates, lipids and proteins. Aside from their nutritious role, proteins have several important functions in seeds, being essential to the molecular biology of the plant. The detailed knowledge of proteins makes it possible to outline strategies of genetic improvement aimed at increasing production and tolerance to different pathologies, among other traits. Progress in the molecular biology, genomics and proteomics impelled the creation of a great volume of data on proteins of several vegetable species, with information about their functionality in the several tissues and organs they are part of. To use this information, it is necessary to rely on computational tools. This need impelled the appearance and development of bioinformatics, e.g. the use of computational tools for the study of biological data. The objective of this work was to quantify the proteins related to the seeds described already and available in the Swiss- Prot database, and to verify the similarity and hydrophobic pattern of the proteins with same function in different species. A detailed consultation was performed in the Swiss-Prot database, in search of proteins found in seeds, seedlings and their component tissues. The sequences found were grouped and analyzed according to the tissue in which they were expressed, epicotyl, aleurone, coleoptile, cotyledon, endosperm, hypocotyl, mesocotyl, immature seed, seedling and seeds. Alignments were performed among the sequences with similar function in different organs and in different species to verify similarities across tissues and species. The hydrophobic/ hydrophilic character in the proteins found was analyzed to identify patterns. Four hundred and fifty seed-related proteins are in stock at the Swiss Prot database. Oryza sativa, Zea mays, Arabidopsis thaliana, Triticum aestivum, Hordeum vulgare, Glycine max, which are the species that possess the largest number of seed proteins studied so far. There isn t a similarity in the sequences of amino acids of the proteins with same function